Baseline predictors of poor clinical outcome despite recanalization of distal middle cerebral artery occlusions - Chafai, Imene; Salim, Hamza; Musmar, Basel; Adeeb, Nimer; Yedavalli, Vivek; ElNaamani, Kareem; Henninger, Nils; Nedelcu, Simona; Sundararajan, Sri Hari; Kühn, Anna Luisa; Khalife, Jane; Ghozy, Sherief; et al. (Interventional neuroradiology, 2025)
Objective - Mechanical thrombectomy (MT) is well-established for the treatment of acute ischemic stroke (AIS) from large vessel occlusion (LVO), with growing data supporting the expansion to distal and medium vessel occlusions (DMVO). Despite successful recanalization in DMVO, certain patients still experience poor long-term clinical outcomes, prompting our study to comprehensively explore pre-MT factors influencing outcome despite excellent recanalization (final modified Thrombolysis in Cerebral Infarction [mTICI] score ≥2c). - Methods - We retrospectively examined data from patients who consecutively underwent MT for a primary middle cerebral artery (MCA) DMVO across 37 centers in North America, Asia, and Europe. We identified baseline clinical and imaging factors associated with poor clinical outcome (defined as a modified Rankin Scale [mRS] score of 3-6) at 3 months, despite excellent recanalization using a multivariable model. - Results - Between September 2017 and July 2021, 623 patients achieved mTICI > 2b and they were included in our study. Among them, 198 (32%) experienced a poor clinical outcome (mRS 3-6). Predictors of poor clinical outcome included higher age (OR 1.05 [1.03-1.07], p < 0.001), higher NIHSS at admission (OR 1.12 [1.08-1.15], p < 0.001), higher baseline mRS (OR 1.77 [0.96-3.26], p = 0.067), and diabetes (OR 1.59 [1.01-2.48], p = 0.044). Higher ASPECTS was associated with a decreased risk of poor clinical outcome (OR 0.82 [0.71-0.94], p = 0.006). - Conclusion - Older age, diabetes, higher baseline mRS, and NIHSS were associated with poor clinical outcome in MCA DMVO despite excellent recanalization. Conversely, a higher ASPECTS decreased the probability of such an outcome.
Gesehen am 12.01.2026